Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease - Badarinarayan, Nandini; Bis, Joshua C; Heilmann-Heimbach, Stefanie; Sleegers, Kristel; Vronskaya, Maria; White, Charles C; Hamilton-Nelson, Kara L; Choi, Seung-Hoan; Forstner, Andreas J; Bacq, Delphine; Brody, Jennifer A; Wolters, Frank J; et al. (Nature genetics, 2017)
Sven van der Lee, Julie Williams, Gerard Schellenberg and colleagues identify rare coding variants in PLCG2 , ABI3 and TREM2 associated with Alzheimer's disease. These genes are highly expressed in microglia and provide additional evidence that the microglia-mediated immune response contributes to the development of Alzheimer's disease. We identified rare coding variants associated with Alzheimer's disease in a three-stage case–control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants ( P < 1 × 10 −4 ) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations ( P < 5 × 10 −8 ) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10 −10 , odds ratio (OR) = 0.68, minor allele frequency (MAF) cases = 0.0059, MAF controls = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10 −10 , OR = 1.43, MAF cases = 0.011, MAF controls = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10 −14 , OR = 1.67, MAF cases = 0.0143, MAF controls = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein–protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.